Penguasaan Ilmu Sebagai Syarat Pemimpin Negara Menurut Al-Mawardi dan Imam Al-Ghazali - Irwansyah; Erha Saufan Hadana - (Al-Mizan, 2022)
Talking about the leader figure of course there are many theories that explain the ideal criteria to be a leader, as well as the criteria that were compiled by previous scholars. Specifically in this study, the author wants to see and know the views of Al-Mawardi and Al-Ghazali regarding mastery of science as a condition for state leaders. The research method used is a descriptive method with a research design using a library method and a doctrinal normative approach, explaining one research variable, namely mastery of knowledge as a condition for state leaders according to Al-Mawardi and Al-Ghazali. The instrument used is the work of Al-Mawardi, namely Al-Ahkam Al-Sulthaniyyah and the work of Al-Ghazali, namely, Tibrul Al-Masbuk fi Nashihah Al-Muluk. The data analysis technique used in this research is qualitative content analysis. Namely, describe the data obtained clearly and take its contents using a critical analysis perspective. Thus, it can be concluded that; first, Ahlul Ijtihad is a fiqh expert (Islamic jurist) who mobilizes all his power and ability to obtain syar'i legal status; second, Al-Mawardi and Al-Ghazali have the same view in terms of the state leader must have knowledge, while both have different views in terms of the science referred to by Al-Mawardi requires a state leader at the mujtahid level while the science referred to by Al-Mawardi Ghazali does not require a state leader to be at the level of a mujtahid, but it is also permissible for a state leader to be a mujtahid.